Confronting the difficult challenges of academic reading of Indonesian graduate students through the lens of self-efficacy and metacognitive strategies - Elizabeth Emmanuela Sulistyawati; Concilianus Laos Mbato (Journal on English as a Foreign Language, 2022)
Students’ self-efficacy and reading strategies have been globally investigated. However, there is a limited number of studies in Indonesia that examined the correlation between self-efficacy and metacognitive reading strategies. This study aimed to find out the correlation between students’ self-efficacy and metacognitive reading strategies, their perceptions of self-efficacy, and their metacognitive strategies. This mixed-method study used a Likert scale questionnaire and interview to collect the data. From the quantitative data analysis, the results show that there is a positive correlation between students’ self-efficacy and metacognitive reading strategies of the Indonesian graduate students, which was significant at the 0.01 level (r = .970, n = 33). The students used the most metacognitive strategies in every stage of reading to a high degree. They also shared different strategies used when students encountered difficulties (St. 5, M=4.12). From the qualitative data analysis, the students applied four different strategies for each reading stage. They also shared the different reasons concerning the use of metacognitive reading strategies. This current study offers one major implication. Since the students’ levels of self-efficacy are affected by extrinsic aspects, teachers need to develop a professional identity that enables them to support students in developing self-beliefs and metacognitive reading strategies.